Optimizing the use of recycled glass materials in alkali activated cement (AAC) based mortars. (10th May 2020) - Zhang, Binyu; He, Pingping; Poon, Chi Sun
Abstract: The management of waste glass generated mainly from waste glass beverage bottles has become a pressuring waste management problem. This study presents a novel way to incorporate recycled glass materials into alkali-activated cement (AAC) based pastes/mortars. Waste glass cullet (GC) was used to replace natural aggregates and waste glass powder (GP) was used to partially replace conventional precursors such as ground blast furnace slag (GGBS). Optimization was conducted innovatively aiming at maximizing the total waste glass content in the AAC materials while maintaining adequate mechanical, durability and functional properties of the final products that contained more than 70% of recycled glass materials by mass. Using the developed technology, recycled glass incorporated alkali activated cement based mortars (AAMs) with a 28-day compressive strength of about 40 MPa can be produced. Furthermore, the excellent high temperature resistance of the optimized AAC mortar mixture allowed the retention of over 50% of the original strength after 2 h of exposure at 800 °C. The experimental results also showed that the detrimental expansion caused by the alkali silica reaction (ASR) between the alkali and the waste GC in the AAC mortars could be controlled successfully by using additional aluminium sources such as calcium aluminate cement (CAC). Further reduction in ASR expansion was possible via adjusting the GC to binder ratio. Also, the drying shrinkage level could be controlled to less than 1000με which is a significant improvement to conventional AAC materials prepared by using GGBS. The findings presented in this paper are pivotal for maximizing the recycling and reusing of waste glass in AAC. Highlights: The feasibility of preparing recycled glass dominated AAMs is proven. The high temperature resistance capacity of Glass-AAMs is systemically evaluated. An effective ASR expansion suppression method for Glass-AAMs is provided.